ANALISIS KEBUTUHAN DIKLAT (AKD) BAGI APARATUR DI LINGKUNGAN PEMERINTAH PROVINSI RIAU - ', Kiswanto; ', Zainuri; ', Gevisioner; Harahap, Heryudarini (Universitas Riau, 2017)
The need to improve the competence of human resources needs to get serious attentithe local government. The human resources is a resources or operates other r available within the organization. Alternative programs commonly used by an organiz improve the capability or competence or human resources is education and training ( The high demands of increasing the competence of apparatus in every SKPD in the Government of Riau bring the consequences to the many need education and training. all the needs of the competences of development that match with the specifications an of the job in the field is certainly difficult to fulfill everything.This is due to various limitations, including a) Limited funds for education and trai Limited facilities and infrastructure of training institutions, and c) Limited man human resources. Paying attention to Mid-Term Plan Develompent (RPJM) of Riau2014-2019 (Bappeda of Riau Province, 2014), it can be put forward the priority ag fulfilling the needs of competence development for the apparaturs in the environme provincial government.